Development and validation of the student ratings in clinical teaching scale in Australia: a methodological study. (Journal of Educational Evaluation for Health Professions, 2023)
Purpose: This study aimed to devise a valid measurement for assessing clinical students' perceptions of teaching practices. Methods: A new tool was developed based on a meta-analysis encompassing effective clinical teaching-learning factors. Seventy-nine items were generated using a frequency (never to always) scale. The tool was applied to the University of New South Wales year 2, 3, and 6 medical students. Exploratory and confirmatory factor analysis (exploratory factor analysis [EFA] and confirmatory factor analysis [CFA], respectively) were conducted to establish the tool's construct validity and goodness of fit, and Cronbach's α was used for reliability. Results: In total, 352 students (44.2%) completed the questionnaire. The EFA identified student-centered learning, problem-solving learning, self-directed learning, and visual technology (reliability, 0.77 to 0.89). CFA showed acceptable goodness of fit (chi-square P<0.01, comparative fit index=0.930 and Tucker- Lewis index=0.917, root mean square error of approximation=0.069, standardized root mean square residual=0.06). Conclusion: The established tool--Student Ratings in Clinical Teaching (STRICT)--is a valid and reliable tool that demonstrates how students perceive clinical teaching efficacy. STRICT measures the frequency of teaching practices to mitigate the biases of acquiescence and social desirability. Clinical teachers may use the tool to adapt their teaching practices with more active learning activities and to utilize visual technology to facilitate clinical learning efficacy. Clinical educators may apply STRICT to assess how these teaching practices are implemented in current clinical settings.